Repair or Degrade: the Thermodynamic Dilemma of Cellular Protein Quality-Control - Fauvet, Bruno; Rebeaud, Mathieu E.; Tiwari, Satyam; De Los Rios, Paolo; Goloubinoff, Pierre (Frontiers in Molecular Biosciences, 2021)
Life is a non-equilibrium phenomenon. Owing to their high free energy content, the macromolecules of life tend to spontaneously react with ambient oxygen and water and turn into more stable inorganic molecules. A similar thermodynamic picture applies to the complex shapes of proteins: While a polypeptide is emerging unfolded from the ribosome, it may spontaneously acquire secondary structures and collapse into its functional native conformation. The spontaneity of this process is evidence that the free energy of the unstructured state is higher than that of the structured native state. Yet, under stress or because of mutations, complex polypeptides may fail to reach their native conformation and form instead thermodynamically stable aggregates devoid of biological activity. Cells have evolved molecular chaperones to actively counteract the misfolding of stress-labile proteins dictated by equilibrium thermodynamics. HSP60, HSP70 and HSP100 can inject energy from ATP hydrolysis into the forceful unfolding of stable misfolded structures in proteins and convert them into unstable intermediates that can collapse into the native state, even under conditions that are inauspicious for the native state. Aggregates and misfolded proteins may also be unfolded and degraded by chaperone-gated endo-cellular proteases, and in eukaryotes also by chaperone-mediated autophagy paving the way for their replacement by new, unaltered functional proteins. The greater energy cost of degrading and replacing a polypeptide with respect to the cost of its chaperon-mediated repair represents a thermodynamic dilemma: some easily repairable proteins are better processed by chaperones while it would be wasteful to uselessly try to recover overly compromised ones, which are instead better degraded and replaced. Evolution has solved this conundrum by creating a host of chaperones and degradation machines and by tuning their cellular amounts and activity rates.